2007
DOI: 10.1080/13697130701624757
|View full text |Cite
|
Sign up to set email alerts
|

Uterotropic effects of dietary equol administration in ovariectomized Sprague–Dawley rats

Abstract: Long-term high-dose dietary equol administration to ovariectomized rats exerts uterotropic effects at the cellular and molecular level which question the safety of uncontrolled and unlimited consumption of soy or red clover supplements by postmenopausal women with intact uteri.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 51 publications
2
15
0
3
Order By: Relevance
“…Our current weight gain data support those of others showing an attenuation of BW following E 2 supplementation in OVX rats (Cooke & Naaz 2004, Rachon et al 2007a. However, no such effects were observed with SPI feeding.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our current weight gain data support those of others showing an attenuation of BW following E 2 supplementation in OVX rats (Cooke & Naaz 2004, Rachon et al 2007a. However, no such effects were observed with SPI feeding.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, current findings and our previous data demonstrate that SPI feeding does not elicit classical estrogenic responses on ERa-responsive tissues such as the uterus, even when utilized as the sole protein source. By contrast, mature OVX rats fed purified equol (400 mg/kg) or injected with purified genistein (54 mg/kg) displayed mild estrogen-like uterine stimulation (Rachon et al 2007a, Rimoldi et al 2007. Studies utilizing purified soy isoflavones were shown to regulate gene expression similar to estrogens in female (Naciff et al 2002) and male reproductive tissues (Naciff et al 2004(Naciff et al , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were orally gavaged for 5 consecutive days with olive oil (1 ml/rat/day) as the vehicle control group, equol low dose (100 mg/kg BW/day), equol high dose (250 mg/kg BW/day), and flutamide (100 mg/kg BW/day) as the anti-androgenic reference positive control group. The low dose equol was determined due to it being the level at which estrogenic effects were observed in ovariectomized rats, but that did not result in negative toxicity [31,32], and was also equivalent to the effective dose of flutamide. The high dose equol was chosen to investigate if the possible androgen antagonistic effects could be detected with a pharmacologically relevant dose.…”
Section: Experimental Designmentioning
confidence: 99%
“…Cross-sectional analysis showed an improvement in bone mineral density for postmenopausal, but not premenopausal women. Rachoń et al (2007b) demonstrated a biphasic effect; dietary EQO administration had no effect in the proximal tibial metaphysis, while an enhancement was seen in the lumbar spine of rats. However, according to Setchell and Cole's theory (2006), the clinical effectiveness of soy protein may be a function of its ability to transform soy isofl avones to the more potent EQO.…”
Section: Discussionmentioning
confidence: 89%